2012
DOI: 10.1155/2012/674981
|View full text |Cite
|
Sign up to set email alerts
|

Familial Bell’s Palsy: A Case Report and Literature Review

Abstract: Objective. To describe a unique case of familial Bell's palsy and summarize the current literature regarding possible hereditary influences. Design. Case report. Main Outcome Measures. Clinical exam, CSF analysis, and family history provided per the patient. Results. We report the case of a 58-year-old female who presented with recurrent and bilateral episodes of facial palsy. The patient underwent multiple CSF investigations to rule out a possible infectious and rheumatologic etiology that were all negative. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Based on research conducted by Finsterer in 2008 and Greco in 2012 stated that there was no difference in prevalence by gender. [8,9] From this study, it was found that the most subjects suffering from Bell's palsy were in the rainy season as many as 16 patients (51.6%) and the lowest summer was 7 patients (22.6%). Research conducted by Campbell in 2002, stated that the incidence of sufferers of Bell's palsy in winter (November-March) was higher, while the incidence in summer was low.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Based on research conducted by Finsterer in 2008 and Greco in 2012 stated that there was no difference in prevalence by gender. [8,9] From this study, it was found that the most subjects suffering from Bell's palsy were in the rainy season as many as 16 patients (51.6%) and the lowest summer was 7 patients (22.6%). Research conducted by Campbell in 2002, stated that the incidence of sufferers of Bell's palsy in winter (November-March) was higher, while the incidence in summer was low.…”
Section: Discussionmentioning
confidence: 68%
“…Exposure to cold air can trigger activation of herpes simplex virus type 1 (HSV-1) and prolonged exposure to cold outside can cause vasomotor changes in the facial area, ranging from edematous neuritis to ischemic reflexes. [8] From this study, it was found that the most Bell's palsy subjects were in the 46-55 year old group, namely 11 people (35.5%) and the lowest was in the 0-5 year old and 5-11 year age group, namely 0. From the research made by Finsterer in 2008 and Annsilva in 2010 show that, the peak incidence occurs between the second and fourth decades (15-45 years).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Idiopathic facial nerve paralysis, also known as Bell's palsy (BP) remains the commonest cause of lower motor neuron (LMN) facial palsy, accounting for about 60-70% of all cases of unilateral facial palsy [1]. Although there are many other causes, familial facial palsy is uncommon and accounts for about 4-14% of cases [2]. Familial facial palsy or hereditary congenital facial palsy (HCFP) presents with different modes of inheritance, with two genes, HCFP1 and HCFP2 in cases with autosomal-dominant inheritance and one gene HCFP3 associated with autosomal recessive inheritance [3].…”
Section: Introductionmentioning
confidence: 99%
“…Sir Charles Bell (1774-1842) de ined paralysis of cranial VII nerve along with its anatomical features and function and hence the disease was named after him as Bell's palsy (Greco et al, 2012). Also known as idiopathic facial paralysis (IFP), around 60-80% of all the lower motor neuron facial palsies are Bell's palsy (Kubik et al, 2012). Of all the facial palsies, around 4-7% cases are of recurrent Bell's palsy (Pitts et al, 1988).…”
Section: Introductionmentioning
confidence: 99%